Elites Educated for European Integration: Juan Churruca Arrellano and the Instituto de Estudios Europeos at the University of Deusto (1979-1987) - Carl Lemke Duque (Espacio, Tiempo y Educación, 2019)
This article focuses on the process of rapprochement between Spain and Europe in the years after Spain’s political transition to democracy and prior to its formal entry into the European Economic Community in 1986. It looks deeply into a concrete case at the regional level, namely the steps taken on the path towards European integration in the Basque Country with the founding of the Instituto de Estudios Europeos at the University of Deusto (Bilbao). The European issues taught at the Institute centered on technical and administrative elements, contributing to the education of a rather functional elite capable of responding to practical needs related to Spain’s European integration. This article will first analyze the perspective of the Institute’s founding-director, Basque-Navarre jurist and politician Juan Churruca Arrellano, looking into his intellectual socialization, as well as his idea of Europe. In this respect, Churruca followed an Ortegian conception of Europe, that is, a historical and cultural understanding of Europe very present in Spain’s intellectual, cultural and political elite during that time. Furthermore, this study delves into the immediate political-historical context surrounding the Institute’s foundation, paying particular attention to the relationship between Churruca and the University of Deusto in terms of national and regional politics. Finally, in the conclusion, this paper outlines an answer to the question of how the Instituto de Estudios Europeos contributed to Spain’s initial European integration.